HOMESCHOOLING FOR TWICE EXCEPTIONALITY IN THE FILM THE MIRACLE WORKER IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Wahyu Nisawati Mafrukha (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: The Miracle Worker has described about the life story of Hellen Keler. A little girl that hasa special needs because of deaf, dumb and blind, but she is smart.Individuals who are talented but alsoat the same time identified as children who have special needs due to disability children with twice exceptionality. The educational program for children with twice exceptionality there are many. One of those isthrough the homeschooling program. Based on the background that have been described above, the author formulates the problem "How Homeschooling For Twice Exceptionality in The Film The Miracle Worker in The Perspective of Islamic Education?". The purpose of this research is to find out and describe clearly about the method in the Homeschooling which are contained in The film The Miracle Worker based on slamic Educational Perspective. The type of research that the author use is a library research. Because the author's materials are from books, scientific magazines, documents and other material that can be a source of reference in this research.The method of thinking which authors use in this research are inductive and deductive methods. The objects in this research is Homeschooling in Islamic educational perspective which are contained in The film The Miracle Worker. Based on allthe above presentation, it can be concluded by the results of the analysis that in the film The Miracle Worker, learning methods that used in the homeschooling is using approach to the teories of human development; cognitive, behavioraltheory (behavioristic) and social learning theory. In educating Helen, Mrs. Sullivan managed to approach using all three theories. In Islamic education, the human development theories such as cognitive, behavioristic and social learning theories are correlated with Islamic education methods. Keyword:. Homeschooling, Exceptional Twice, Pendidikan Islam.